Effect of E-Readiness Skills, Metacognitive Awareness, and Biological Literacy on the High School Students' Misconceptions - J. Jamaluddin; A. W. Jufri; A. Ramdani (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to determine the effect of e-readiness skills, metacognitive awareness, and biological literacy on students’ misconceptions about the ecosystem concept. This type of research is quantitative descriptive with a survey method. The research subjects were 182 West Lombok high school students Regency. Data collection used an e-readiness questionnaire, MAI inventory, and a biological literacy test combined with the CRI method. Data analysis used descriptive analysis techniques and multiple regression analysis. The data analysis using multiple regression analysis with the help of the SPSS 26 program obtained the following results: partial multiple linear regression analysis found that e-readiness skills (sig. 0.0000.05) and biological literacy (sig. 0.0070.05) have a significant effect on students’ misconceptions, while metacognitive awareness (sig 0.0880.05) does not affect students’ misconceptions. This study concluded that partially e-readiness skills and biological literacy had a significant effect on students’ misconceptions, while metacognitive awareness had no significant effect on students’ misconceptions. Simultaneously, e-readiness skills, metacognitive awareness, and biological literacy positively affect high school students’ misconceptions about the ecosystem concept. Biology teachers are expected to pay attention to efforts to improve e-readiness skills, metacognitive awareness, and students’ biology literacy to minimize their misconceptions about biology concepts in high school.